2016
DOI: 10.1037/xge0000156
|View full text |Cite
|
Sign up to set email alerts
|

Once failed, twice shy: How group-based competition influences risk preference in young children.

Abstract: Recent developmental research demonstrates that young children tend to be risk-seeking. However, very little is known about the extent to which such a capacity varies with children's group-based experience. Given that between-group competition is a central feature of human social life, this study aimed at examining the influence of group-based competition over risk preference in young children. In total, 234 children from 3 age groups (2-4-year-olds, 5-6-year-olds, and 8-9-year-olds) engaged in an intergroup c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
5
19
1
Order By: Relevance
“…Intriguingly, compared to winners or control participants who performed the task without inter-group competition, it was observed that losers became risk-averse. This differs from our results, and this might be explained by several important differences between the two studies, including the age of participants (adolescents aged 14–15 in the current experiment vs. children 2–9 years old in Zhu et al, 2016), inter-individual vs. inter-group competition, multiple choices with risky options made during and affecting the competition vs. a single choice made after the competition, and whether the ranks (winning/losing) presented were fake or real. Exploring how these factors relate to risk-taking tendencies would be important in clarifying the relationships between risky behavior in adolescents and peer competition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, compared to winners or control participants who performed the task without inter-group competition, it was observed that losers became risk-averse. This differs from our results, and this might be explained by several important differences between the two studies, including the age of participants (adolescents aged 14–15 in the current experiment vs. children 2–9 years old in Zhu et al, 2016), inter-individual vs. inter-group competition, multiple choices with risky options made during and affecting the competition vs. a single choice made after the competition, and whether the ranks (winning/losing) presented were fake or real. Exploring how these factors relate to risk-taking tendencies would be important in clarifying the relationships between risky behavior in adolescents and peer competition.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study (Zhu et al, 2016) examined how winning/losing in a task with inter-group competition affects the tendency for risk-taking in subsequent choice opportunities in children. Intriguingly, compared to winners or control participants who performed the task without inter-group competition, it was observed that losers became risk-averse.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that toddlers in Experiment 1 preferred the risky option to the certain option with the same EV suggests that toddlers are risk prone in gain contexts. The current study extends to toddlers the findings providing evidence that risk proneness is a common strategy in children (e.g., Harbaugh et al, ; Paulsen et al, ; van Leijenhorst et al, ; Zhu et al, ). In Experiment 1, findings indicate that mangabeys show a trend to preferentially select the risky option when tested with the carrot reward.…”
Section: Discussionsupporting
confidence: 71%
“…In contrast to human adults, risk proneness in the gain domain is usually observed in both young children and non-human primates (e.g., Harbaugh et al, 2002;Long et al, 2009;McCoy & Platt, 2005;O'Neill & Schultz, 2010;Paulsen et al, 2011;So & Stuphorn, 2010;van Leijenhorst et al, 2010;Xu & Kralik, 2014;Zhu, Wang, Lv, & Li, 2016). It is currently unclear what mechanism might be underlying such economic preferences.…”
Section: Experimental Questions Addressed In This Studymentioning
confidence: 99%
See 1 more Smart Citation